2014
DOI: 10.3109/13651501.2014.979834
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction is related to attention deficit but not hyperactivity in a sample of high school students

Abstract: These results suggest that attention deficit and playing online games are important determinants of IA in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
0
13
1
4
Order By: Relevance
“…deficits were more related to Internet addiction than hyperactivity symptoms [47]. Other studies which focused on FB addiction reported that individuals with reduced self-control were at increased risk [48].…”
Section: Discussionmentioning
confidence: 99%
“…deficits were more related to Internet addiction than hyperactivity symptoms [47]. Other studies which focused on FB addiction reported that individuals with reduced self-control were at increased risk [48].…”
Section: Discussionmentioning
confidence: 99%
“…Nove (75%) dos 12 estudos foram resgatados na base de pesquisa multidisciplinar Scopus, dois exclusivamente na PsycINFO (16,7%) e um na Cinahl (8,3%). Entre os artigos analisados, sete (58,3%) foram publicados em revistas da área específica da psiquiatria [12][13][14][15][16][17][18] , dois (16,7%), da pediatria 19,20 , um (8,3%), da saúde coletiva 21 e dois (16,7%) são periódicos de conhecimento multidisciplinar 22,23 . Dez estudos utilizaram desenho metodológico transversal e dois, longitudinais 19,23 , com o objetivo de identificar possíveis preditores da DI.…”
Section: Resultsunclassified
“…Dos 12 artigos selecionados, 11 estudos indicaram haver relação entre DI e sintomas de TDAH, mostrando as possíveis associações entre essas condições [12][13][14][15][17][18][19][20][21][22][23] , inclusive quando comparados adolescentes com e sem DI 12,17,22 . Estudos indicaram que, entre várias comorbidades associadas à DI, o TDAH é uma das mais prevalentes 12,13,17 .…”
Section: Relação Entre DI E Tdahunclassified
See 2 more Smart Citations